Bentuk Penyajian Tari Gambyong Dalam Pertunjukan Wayang Kulit Pada Pesta Perkawinan Di Desa Baru - Puja Rahayu; Darmawati Darmawati (CV. Aksara Global, 2024)
This study aims to reveal and describe the form of presentation of Gambyong Dance in shadow puppet performances at weddings in Desa Baru, Ranah Batahan District, West Pasaman Regency. This research is qualitative research with descriptive method of analysis. The research instrument is the researcher himself and is assisted by supporting tools such as stationery and cameras. Data were collected through observation techniques, interviews, literature studies, and documentation. The steps of analyzing are carried out through data collection, data reduction and conclusion making. The results showed that the form of presentation of Gambyong Dance in Desa Baru was collaborated with a shadow puppet performance that told about Arjuna's marriage with Dewi Borosumbroto.Gambyong Dance was performed by 4 female dancers 1 puppeteer. The movements of this Gambyong dance are the Sekaran Rorok Asem movement, the Jamang Trap movement, the Sekaran Kawilan movement, the Egol movement, the Sekaran Kesetan Sampir Sampur movement and the Mentangan Seblak Sampur movement. The floor pattern of Gambyong Dance is a straight line floor pattern and a curved line floor pattern. The accompaniment music of Gambyong Dance is gong, drum, gamelang and telempong with the property of using shawls. The makeup used is beautiful makeup. The costume uses a pink kebaya. Sampur uses a dongker blue sampur. Gambyong dance is performed in the wedding party area, which is in the yard of the house that holds the wedding party.